2020
DOI: 10.1111/epi.16670
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress increases inflammatory cytokines in an epilepsy mouse model Gabrg2+/Q390X knockin: A link between genetic and acquired epilepsy?

Abstract: Objective: Neuroinflammation is a major theme in epilepsy, which has been characterized in acquired epilepsy but is poorly understood in genetic epilepsy. γ-Aminobutyric acid type A receptor subunit gene mutations are significant causes of epilepsy, and we have studied the pathophysiology directly resulting from defective receptor channels. Here, we determined the proinflammatory factors in a genetic mouse model, the Gabrg2 +/Q390X knockin (KI). We have identified increased cytokines in multiple brain regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Additionally, the Gabrg2 +/Q390X mice had increased mortality and impaired cognition compared to the Gabrg2 +/− mouse with a loss-of-function mutation in the same protein that did not cause ER stress [60,78]. Importantly, we identified increased neuroinflammation in the Gabrg2 +/Q390X mice but not in the Gabrg2 +/− mouse without ER stress [79]. The loss-of-function model has only mild epilepsy with normal cognition.…”
Section: Endoplasmic Reticulum (Er) Stress Exists In Both Ge and Admentioning
confidence: 72%
See 2 more Smart Citations
“…Additionally, the Gabrg2 +/Q390X mice had increased mortality and impaired cognition compared to the Gabrg2 +/− mouse with a loss-of-function mutation in the same protein that did not cause ER stress [60,78]. Importantly, we identified increased neuroinflammation in the Gabrg2 +/Q390X mice but not in the Gabrg2 +/− mouse without ER stress [79]. The loss-of-function model has only mild epilepsy with normal cognition.…”
Section: Endoplasmic Reticulum (Er) Stress Exists In Both Ge and Admentioning
confidence: 72%
“…The study on Gabrg2 +/Q390X mice implicates that mutant protein accumulation may exist from the beginning of life, although the protein aggregates will not emerge until later in life [30]. Importantly, increased neuroinflammation due to ER-retained mutant protein was observed in knockin mouse pups carrying the GABRG2(Q390X) mutation, suggesting that underlying changes occur long before any symptom emerges [79]. The efficacy of memantine in epilepsy and cognitive improvement with GRIN2A mutations does a good job of explaining why the blockade of NMDA receptors is beneficial for AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, expression of Icam1 was significantly up-regulated in the hippocampi with hippocampal sclerosis ( Nakahara et al, 2010 ). Interleukin-6 (Il6) is a prototypical proinflammatory cytokine for maintaining homeostasis, and animal experiments showed the involvement of cytokines in epilepsy ( Shen et al, 2020 ). The previous report has revealed that an increased level of IL6 was observed in cerebrospinal fluid and serum from patients with epilepsy ( Peltola et al, 1998 ; Tao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that neuroinflammation is the pathological signature of central nervous system diseases including epilepsy (Galan, 2021;Devinsky et al, 2013;Vezzani et al, 2013). Proinflammatory cytokines such as tumor necrosis factor alpha, interleukin 1-beta (IL-1β), and IL-6 were increased in the Gabrg2 +/Q390X knockin mice, providing the first link of neuroinflammation between genetic epilepsy associated with an ion channel gene mutation and acquired epilepsy (Shen et al, 2020). Astrocytes are characteristic glial cells responsible for nutrition support, blood-brain barrier formation, extracellular ion equilibrium, and synaptic plasticity (Karve et al, 2016;Araki et al, 2021).…”
Section: Introductionmentioning
confidence: 99%